Note on the exponential recursive k -ary trees - Ghasemi, Mina; Javanian, Mehri; Nabiyyi, Ramin Imany (RAIRO. Informatique théorique et applications, 2023)
In the present paper, we consider exponential recursive trees with no node of outdegree greater than k , called exponential recursive k -ary trees ( k ≥ 2). At each step of growing of these trees, every external node (insertion position) is changed into a leaf with probability p , or fails to do so with probability 1 — p . We investigate limiting behavior of fundamental parameters such as size, leaves and distances in exponential recursive k -ary trees.